Genome-wide analysis in endangered populations: a case study in Barbaresca sheep. (12th January 2017) - Mastrangelo, S.; Portolano, B.; Di Gerlando, R.; Ciampolini, R.; Tolone, M.; Sardina, M. T.
Abstract : Analysis of genomic data is becoming increasingly common in the livestock industry and the findings have been an invaluable resource for effective management of breeding programs in small and endangered populations. In this paper, with the goal of highlighting the potential of genomic analysis for small and endangered populations, genome-wide levels of linkage disequilibrium, measured as the squared correlation coefficient of allele frequencies at a pair of loci, effective population size, runs of homozygosity (ROH) and genetic diversity parameters, were estimated in Barbaresca sheep using Illumina OvineSNP50K array data. Moreover, the breed's genetic structure and its relationship with other breeds were investigated. Levels of pairwise linkage disequilibrium decreased with increasing distance between single nucleotide polymorphisms. An average correlation coefficient <0.25 was found for markers located up to 50 kb apart. Therefore, these results support the need to use denser single nucleotide polymorphism panels for high power association mapping and genomic selection efficiency in future breeding programs. The estimate of past effective population size ranged from 747 animals 250 generations ago to 28 animals five generations ago, whereas the contemporary effective population size was 25 animals. A total of 637 ROH were identified, most of which were short (67%) and ranged from 1 to 10 Mb. The genetic analyses revealed that the Barbaresca breed tended to display lower variability than other Sicilian breeds. Recent inbreeding was evident, according to the ROH analysis. All the investigated parameters showed a comparatively narrow genetic base and indicated an endangered status for Barbaresca. Multidimensional scaling, model-based clustering, measurement of population differentiation, neighbor networks and haplotype sharing distinguished Barbaresca from other breeds, showed a low level of admixture with the other breeds considered in this study, and indicated clear genetic differences compared with other breeds. Attention should be given to the conservation of Barbaresca due to its critical conservation status. In this context, genomic information may have a crucial role in management of small and endangered populations.